2017
DOI: 10.1371/journal.ppat.1006587
|View full text |Cite|
|
Sign up to set email alerts
|

The replication initiator protein of a geminivirus interacts with host monoubiquitination machinery and stimulates transcription of the viral genome

Abstract: Geminiviruses constitute a group of plant viruses, with a ssDNA genome, whose replication in the nucleus of an infected cell requires the function of geminivirus-encoded replication initiator protein (Rep). Our results suggest that monoubiquitinated histone 2B (H2B-ub) promotes tri-methylation of histone 3 at lysine 4 (H3-K4me3) on the promoter of Chilli leaf curl virus (ChiLCV). We isolated homologues of two major components of the monoubiquitination machinery: UBIQUITIN-CONJUGATING ENZYME2 (NbUBC2) and HISTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 91 publications
1
40
0
1
Order By: Relevance
“…Viral proteins also routinely undergo PTMs to modulate infection. Recently, many geminiviral proteins (βC1, Rep, AC4, AV1) have been shown to undergo PTMs directly (Kushwaha et al, 2017;Shen et al, 2011;Li et al, 2018;Chowda-Reddy et al, 2008). We observed SyYVCV βC1 has multiple predicted SUMOylation consensus motifs as well as SIMs ( Figure 1A).…”
Section: Discussionmentioning
confidence: 52%
“…Viral proteins also routinely undergo PTMs to modulate infection. Recently, many geminiviral proteins (βC1, Rep, AC4, AV1) have been shown to undergo PTMs directly (Kushwaha et al, 2017;Shen et al, 2011;Li et al, 2018;Chowda-Reddy et al, 2008). We observed SyYVCV βC1 has multiple predicted SUMOylation consensus motifs as well as SIMs ( Figure 1A).…”
Section: Discussionmentioning
confidence: 52%
“…NbPI4KII was expressed as in‐frame fusion with the N‐terminal of the YFP protein using the pSPYNE vector. ChiLCV Rep protein was expressed with C‐terminal region of the YFP protein using pSPYCE vector (Kushwaha et al ., ). Bimolecular fluorescence complementation (BiFC) assays of interaction of (A) pSPYNE‐NbPI4KII and pSPYCE‐Rep, (B) pSPYNE‐ NbPI4KII and pSPYCE, (C) pSPYNE and pSPYCE‐Rep and (D) pSPYNE / pSPYCE.…”
Section: Resultsmentioning
confidence: 97%
“…To study the effect of ChiLCV Rep protein on the subcellular localization of NbPI4KII or vice versa, a co‐localization study was performed by co‐expressing NbPI4KII ‐mGFP and 35S: C1 ‐ DsRed . Nuclear localization of ChiLCV Rep‐DsRed has already been reported (Kushwaha et al ., ). The subcellular localization study revealed that Rep‐DsRed was confined to the nucleus in the presence of NbPI4KII‐mGFP.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations